Lipid profile with fasting glucose in individuals with type 2 diabetes mellitus, Trinidad, Bolivia - Olmos Mostacero, Judith Margarita (2024)
Objective. To relate the lipid profle of individuals with type 2 diabetes mellitus at the Hospital "Presidente German Busch" in Trinidad (Bolivia), during the 2023 period. Methods. A total of 530 individuals were studied using a quantitative approach, with an analytical, descriptive, observational, retrospective, and cross-sectional design. Data collection was performed from secondary sources, using content analysis of laboratory blood chemistry records. Spearman's correlation coefficient was applied for statistical analysis. Results. 43% of the individuals with elevated fasting glucose and lipid profle levels were women. The mean total cholesterol was 158 mg/dL (95% CI = 153.29 to 162.92), the mean triglycerides were 171 mg/dL (95% CI = 161.15 to 181.08), the mean HDL-C was 37 mg/dL (95% CI = 35.62 to 38.99), the mean LDL-C was 92 mg/dL (95% CI = 88.63 to 96.31), and the mean VLDL-C was 34 mg/dL (95% CI = 32.02 to 35.99). A relationship was found between the lipid profle and fasting glucose (rho = 0.146, p < 0.001). Furthermore, there was a correlation between the lipid profile and sex (rho = 0.113, p = 0.009). Conclusions. A significant relationship exists between the lipid profle and fasting glucose, and between the lipid profle and sex; however, there is no correlation with age group